High-speed spin measurement system for dotted table tennis ball using single-frame M-sequence multi-exposures - Tomohiro Sueishi; Himari Tochioka; Masatoshi Ishikawa (SICE Journal of Control, Measurement, and System Integration)
Spin information in table tennis is useful and necessary for improving play and controlling table tennis robots because it can significantly change the trajectory of the ball. However, the spin speed is very high, reaching 150 rps, and it is difficult to measure the spin accurately and at high speed even with a high-speed camera at 1,000 fps. In this paper, we propose a high-speed table tennis spin measurement system using single-frame multi-exposures based on M-sequence patterns and symmetric dot markers. We have experimentally evaluated that the system has sufficient measurement accuracy and a computation speed of more than 500 fps for simulated images with various spin amounts, axes, and viewing angles. We have also demonstrated the sufficient measurement performance of 90 rps spins of a real moving table tennis ball attached to a motor in a combination with a high-speed pan-tilt system using galvanometer mirrors.